PENGEMBANGAN MEDIA FLASHCARD AUGMENTED REALITY PADA MATERI KEKAYAAN BUDAYA INDONESIA KELAS IV - Ayu Ningsih, Santi; Santa; Herawati, Desti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Santi Ayu Ningsih 037121062. "DEVELOPMENT OF AUGMENTED REALITY FLASHCARD MEDIA ON INDONESIAN CULTURAL WEALTH MATERIAL GRADE IV" grade IV students at Ciriung State Elementary School 02 Cibinong. It aims to develop Augmented Reality (AR) flashcard media and find out its influence on students' learning outcomes on Indonesian Cultural Wealth material. This research uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The validation of learning media is carried out by five experts, namely media experts, linguists, lecturer material experts, teacher material experts, and evaluation experts. There are results of validation of the revised results, namely from media validation of 100%, language validation of 100%, validation of material by lecturers of 96%, and validation of material by teachers of 90%, and validation of evaluation of 96% with an average overall result of 96.4% with very feasible criteria. For the results, the N-Gain score obtained an average score of 0.78 with high criteria. The results of the students' questionnaire response with an average of 93% were very good and the teacher's questionnaire response of 85% was also very good. Thus, it can be concluded that Augmented Reality (AR) flashcard media is very feasible and effective in improving student learning outcomes, especially in Indonesian Cultural Wealth materials.